Application of Relating, Experiencing, Applying, Cooperating, Transferring (REACT) Learning Models Based on Riau Malay Culture on the Ability to Use Mathematical Problems of Junior High School Students - Suraji, Suraji; Zulkarnain, Zulkarnain; Saragih, Sehatta (FKIP - Universitas Riau, 2020)
This study aimed to examine comprehensively the effect of the application of REACT learning models based on the Malay cultural context of Riau on students’ mathematical problem-solving abilities. The research was a quasi-experimental research with Pretest-post-test control group design. The sample of this study was all students of class VII SMP 12 Pekanbaru. The results of data analysis were: (1) There was a difference of the mathematical problem-solving ability of Pekanbaru junior high school students between who learned to use REACT learning models based on the Malay cultural context of Riau and students who studied with conventional learning; (2) There was a difference of the mathematical problem-solving ability of Pekanbaru junior high school students between who learned to use REACT learning models based on the Malay cultural context of Riau and students who studied with conventional learning in terms of aspects of student ability levels, (3) There was no interaction between the learning model and the level of students’ ability to the ability to solve mathematical problems; (4) There was a difference in the mathematical problem-solving ability of Pekanbaru junior high school students who learned to use the REACT learning model based on the Malay Malay cultural context in terms of aspects of student ability levels.